Applied Mechanics and Civil Engineering : Selected, peer reviewed papers from the 2011 SREE Workshop on Applied Mechanics and Civil Engineering (AMCE 2011), December 17-18, 2011, Macau (Applied mechanics and materials, 2011)
The 77 selected papers on Applied Mechanics and Civil Engineering are divided into the topics of: applied mechanics, civil engineering, hydraulic engineering, environmental engineering and safety, others. The work provides an excellent overview of these topics. Review from Book News Inc.: The 77 selected and peer-reviewed papers in this collection cover applied mechanics, civil engineering, hydraulic engineering, and environmental engineering and safety. Among the specific topics are a numerical study on hydrodynamic behavior of deepwater spar platform with different mooring configurations, the effect of bridge-soil interaction on the behavior on an integral bridge, hydraulic characteristics of a cutthroat flume in an irrigation district, ground-based microwave radiometer profiler observations before a heavy rainfall, and the fuzzy finite element optimization of high-speed vertical machining center spindle box. (Annotation ©2012 Book News Inc. Portland, OR).